EVALUASI KINERJA PDAM TIRTA DHARMA KABUPATEN JEPARA - Kholid Fajar Saputra; Yuwanto .; Sulistyowati . (Journal of Politic and Government Studies, 2013)
Performance evaluation is one of the main functions of the management system,particularly management. The evaluation relates to individual performance and managementfor career development and organizational growth. Performance evaluation associated withPDAM is benchmark to observe the regional company's contribution particularly that thecompany performance indicated how far it goes. The way is through the establishment ofBUMD or Perusda. It becomes a trend in various regions. Some of them apply the name, andothers use other similar name. Perusda establishment or BUMD refers to the constitutionnumber 32 of 2004 about regional autonomy along with the based local regulation.Notice that the performance of BUMD for the economy in the area is very interestingdiscourse to be studied more deeply, especially in regional autonomy era presently whichdemands enhancement performance of local government in order to be able to sustain theindependence of the region and to improve the welfare of society without depending supportfrom central government. The existence of BUMD at this time whether they can be expectedto notice at the empirical data on prevalent development. Because of relying on equitybudget, moreover PDAM in a particular area especially in Jepara should be matched on profitorientation, however it should be more oriented on quality service, and it is able to providehigh quality water that meets health requirements.The research uses a qualitative descriptive approach, to describe a phenomenon thatoccurs, and is intended to describe in detail the findings in the field. In collecting the data, thewriter applies qualitative method through indepth-interview. There is a way how to chooseinformants by using purposive or intentionally chosen for requesting information on peoplewho have been interviewed or contacted before, and so on until the information consideredenough.So basically the performance evaluation and the performance appraisal indeed havecriteria in the evaluation or assessment of an activity, as proposed by William N Dunn:observing to the indicators including: all the indicators are intended to discover a descriptionof the performance evaluation.